2019
DOI: 10.1001/jama.2019.4329
|View full text |Cite
|
Sign up to set email alerts
|

Association of Household Income With Life Expectancy and Cause-Specific Mortality in Norway, 2005-2015

Abstract: IMPORTANCE Examining causes of death and making comparisons across countries may increase understanding of the income-related differences in life expectancy. OBJECTIVES To describe income-related differences in life expectancy and causes of death in Norway and to compare those differences with US estimates. DESIGN AND SETTING A registry-based study including all Norwegian residents aged at least 40 years from 2005 to 2015. EXPOSURES Household income adjusted for household size. MAIN OUTCOMES AND MEASURES Life … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
92
2
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(109 citation statements)
references
References 31 publications
5
92
2
10
Order By: Relevance
“…The question of whether the increase in life expectancy has occurred at a similar pace across population groups has been investigated in a number of studies. In such studies, the focus has often been on the specific question of whether parts of the population remain disadvantaged and are left behind as life expectancy increases [3][4][5][6][7][8][9][10]. Previous research has suggested that improvements in health in recent years have been driven by advances at the upper end of the health distribution, while other parts of the population have lagged behind [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The question of whether the increase in life expectancy has occurred at a similar pace across population groups has been investigated in a number of studies. In such studies, the focus has often been on the specific question of whether parts of the population remain disadvantaged and are left behind as life expectancy increases [3][4][5][6][7][8][9][10]. Previous research has suggested that improvements in health in recent years have been driven by advances at the upper end of the health distribution, while other parts of the population have lagged behind [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Low income is known to be associated with increased ACM across high-income, middle-income and low-income countries and even where health systems are tax funded and provided free at the point of delivery. 22 30 Many underlying mechanisms that link poverty with poorer health outcomes like socio-economic barriers for access to healthy behaviours, and the resulting choice of unhealthy alternatives, exist at population level. 31 32 Universal measures to improve living standards by addressing poverty can create manifold benefits including the promotion of healthy behaviours that can reduce the incidence and improve the control of intermediate metabolic risk factors of common mortality outcomes, and thus improve longevity.…”
Section: Discussionmentioning
confidence: 99%
“…A recent Norwegian study shows that comparable magnitudes apply also to Norway in the same period, i.e. the difference in life expectancy between the richest and poorest 1% was 8.4 years for women and 13.8 years for men, see Kinge et al (2019). Huisman et al (2004) reports substantial differences in mortality by education among older individuals also for other European countries.…”
Section: Mortalitymentioning
confidence: 94%